The model of interaction between research universities, business and government in the USA and possibilities of its application in Kazakhstan - Kuramayeva, Gulnaz (Revista Conrado, 2022)
Research universities have a significant impact on the economic development of the state, the processes of implementation and development of entrepreneurial infrastructure, the development of small businesses through the creation of technology parks and business incubators. Therefore, the creation of research universities in Kazakhstan contributes to the liberation of the country from export dependence on raw materials and ensuring high growth dynamics in processing, intellectually oriented and knowledge-intensive industries. This paper analyzes the problems of interaction of research universities, business and government in the current economic environment of Kazakhstan. Based on the study of US experience of integration of leading universities in the innovative development of the regions discussed ways and means to solve the problem. Keywords: Kazakhstan, the USA, research universities, business, government, education, science. RESUMEN Las universidades de investigación tienen un impacto significativo en el desarrollo económico del estado, los procesos de implementación y desarrollo de la infraestructura empresarial, el desarrollo de las pequeñas empresas a través de la creación de parques tecnológicos e incubadoras de empresas. Por lo tanto, la creación de universidades de investigación en Kazajstán contribuye a la liberación del país de la dependencia de las exportaciones de materias primas y asegura una dinámica de alto crecimiento en las industrias de procesamiento, intelectualmente orientadas e intensivas en conocimiento. Este artículo analiza los problemas de interacción de las universidades de investigación, las empresas y el gobierno en el entorno económico actual de Kazajstán. Con base en el estudio de la experiencia estadounidense de integración de universidades líderes en el desarrollo innovador de las regiones, se discutieron formas y medios para resolver el problema. Keywords: Kazajstán, Estados Unidos, universidades de investigación, empresa, gobierno, educación, ciencia.